Hikers to converge on Cimarron Branch Bank Sunday (Raton, NM Raton Range)
This article is about a group from Raton hiking from Raton to Cimarron for the new branch opening on Sunday.
Newspaper article + photograph of the Cimarron Bank Branch
Mater List Item # 64
File location is in the New Mexico File Cabinets
Keywords: DiLisio, Charles; Allen, Elwanda; DiLissio, Chris; Giampietri, Lena; DiLisio, Al; Trujillo, Priscilla; Trent, Charlene; Cain, Leroy; Sultemeier, William H; Burk, William E. Jr; DiLisio, Joe; Eastman, Frank S; Kain, Leroy; Boyle, T. J; Mutton, Dino; DiLisio, Joseph Jr; Cowan, Claude Sr; Wright, John B; Loughridge, Charles; International State Bank; W. R. Bacon and Sons; Hotel Yucca; Bank To Bank Walk; Walks; Bank Openings; Business Expansions; Hikers; Open Houses; Cimarron, New Mexico; Raton, New Mexico